Desain Mural Sebagai Media Komunikasi Visual Perwujudan Destination Branding Desa Wisata Bongan - Pratama, I Gede Yudha (Jurnal Bahasa Rupa, 2022)
Destination Branding is an effort to identify and introduce the potential of a destination, in order to build the identity of a destination against public perception through information and communication media. Bongan Village is one of the tourist villages in the Tabanan Regency which has the potential for its natural, historical, and cultural wealth that can become a leading tourist destination. So, it is important to realize destination branding for Bongan Tourism Village in order to introduce its superior potential through the right communication media. The purpose of realizing this destination branding is to inflame the superior potential of Bongan Tourism Village to the public and tourists through mural design as a medium of communication. The research method used in realizing this destination branding is by conducting observations and direct field interviews through descriptive methods. With the application of this method, it is known that there is a public space in the Bongan Tourism Village area that is appropriate and worthy of being used as a communication medium, in which a communicative mural design can be implemented. Murals, which are often seen as street art, are a choice of media that can communicate and convey information visually in public spaces.